Zinc Deficiency‐Like Syndrome in Fleckvieh Calves: Clinical and Pathological Findings and Differentiation from Bovine Hereditary Zinc Deficiency. (9th February 2018) - Langenmayer, M.C.; Jung, S.; Majzoub‐Altweck, M.; Trefz, F.M.; Seifert, C.; Knubben‐Schweizer, G.; Fries, R.; Hermanns, W.; Gollnick, N.S.
Abstract : Background: Zinc deficiency‐like (ZDL) syndrome is an inherited defect of Fleckvieh calves, with striking similarity to bovine hereditary zinc deficiency (BHZD). However, the causative mutation in a phospholipase D4 encoding gene ( PLD4 ) shows no connection to zinc metabolism. Objectives: To describe clinical signs, laboratory variables, and pathological findings of ZDL syndrome and their utility to differentiate ZDL from BHZD and infectious diseases with similar phenotype. Animals: Nine hospitalized calves with crusting dermatitis and confirmed mutation in PLD4 and medical records from 25 calves with crusting dermatitis or suspected zinc deficiency. Methods: Prospective and retrospective case series. Results: The 9 calves (age: 5–53 weeks) displayed a moderate to severe crusting dermatitis mainly on the head, ventrum, and joints. Respiratory and digestive tract inflammations were frequently observed. Zinc supplementation did not lead to remission of clinical signs in 4 calves. Laboratory variables revealed slight anemia in 8 calves, hypoalbuminemia in 6 calves, but reduced serum zinc concentrations in only 3 calves. Mucosal erosions/ulcerations were present in 7 calves and thymus atrophy or reduced thymic weights in 8 calves. Histologically, skin lesions were indistinguishable from BHZD. Retrospective analysis of medical records revealed the presence of this phenotype since 1988 and pedigree analysis revealed a common ancestor of several affected calves. Conclusions and Clinical Importance: ZDL syndrome should be suspected in Fleckvieh calves with crusting dermatitis together with diarrhea or respiratory tract inflammations without response to oral zinc supplementation. Definite diagnosis requires molecular genetic confirmation of the PLD4 mutation.